PENGARUH PEMBERIAN PATIENT INFORMATION LEAFLET (PIL) DAN SMS MOTIVASI TERHADAP PENGETAHUAN DAN KEPATUHAN PASIEN DM DENGAN DISLIPIDEMIA - Dania, Haafizah; Saputri, Ginanjar Zukhruf; Faridah, Imaniar Noor (Jurnal Farmasi Indonesia, 2019)
Diabetes mellitus(DM) and dyslipidemia are high prevalence diseases which also as one of risk factors for coronary heart disease. Knowledge and adherence are important factors in the treatment of DM-dyslipidemia either to control blood glucose and cholesterol or to prevent from complications. Education is one of the ways to increase knowledge and adherence. The aim of this research is to determine the impact of intervention (Patient Information Leaflet (PIL) and motivation messages by SMS) to knowledge and adherence of DM-dyslipidemia patients in PKU Muhammadiyah Yogyakarta Hospital. This research is a quasi experimental study with analytical quantitative. The data taken from February 2016 to April 2017 at PKU Muhammadiyah Yogyakarta Hospital. Inclusion criterias in this research are patient with age more than 18 years old, with diagnosed by DM-dyslipidemia, using 1 or more of DM and dyslipidemia medicine, not deaf, and cooperative. Interventions that given to the patients are Patient Information Leaflet (PIL) and motivation messages by SMS which routinely given in a week after first we met. Knowledge is assessed using questionnaire and adherence is assesed using pill count method. The data that need analyzed are characteristic patients and the impact of intervention using Wilcoxon and paired t-test. The result of intervention in 56 patients showed the increasing number of patient that have good knowledge after intervention, from 58,9% to 71,4%, otherwise it not differ significantly (p 0.071). Other than that, the adherence also increased that showed from the patients who have adhere category after intervention, from 58,93% to 91.07% and it differ significantly with p 0.001 (p<0.05). Diabetes mellitus(DM) and dyslipidemia are high prevalence diseases which also as one of risk factors for coronary heart disease. Knowledge and adherence are important factors in the treatment of DM-dyslipidemia either to control blood glucose and cholesterol or to prevent from complications. Education is one of the ways to increase knowledge and adherence. The aim of this research is to determine the impact of intervention (Patient Information Leaflet (PIL) and motivation messages by SMS) to knowledge and adherence of DM-dyslipidemia patients in PKU Muhammadiyah Yogyakarta Hospital. This research is a quasi experimental study with analytical quantitative. The data taken from February 2016 to April 2017 at PKU Muhammadiyah Yogyakarta Hospital. Inclusion criterias in this research are patient with age more than 18 years old, with diagnosed by DM-dyslipidemia, using 1 or more of DM and dyslipidemia medicine, not deaf, and cooperative. Interventions that given to the patients are Patient Information Leaflet (PIL) and motivation messages by SMS which routinely given in a week after first we met. Knowledge is assessed using questionnaire and adherence is assesed using pill count method. The data that need analyzed are characteristic patients and the impact of intervention using Wilcoxon and paired t-test. The result of intervention in 56 patients showed the increasing number of patient that have good knowledge after intervention, from 58,9% to 71,4%, otherwise it not differ significantly (p 0.071). Other than that, the adherence also increased that showed from the patients who have adhere category after intervention, from 58,93% to 91.07% and it differ significantly with p 0.001 (p<0.05). Diabetes mellitus(DM) and dyslipidemia are high prevalence diseases which also as one of risk factors for coronary heart disease. Knowledge and adherence are important factors in the treatment of DM-dyslipidemia either to control blood glucose and cholesterol or to prevent from complications. Education is one of the ways to increase knowledge and adherence. The aim of this research is to determine the impact of intervention (Patient Information Leaflet (PIL) and motivation messages by SMS) to knowledge and adherence of DM-dyslipidemia patients in PKU Muhammadiyah Yogyakarta Hospital. This research is a quasi experimental study with analytical quantitative. The data taken from February 2016 to April 2017 at PKU Muhammadiyah Yogyakarta Hospital. Inclusion criterias in this research are patient with age more than 18 years old, with diagnosed by DM-dyslipidemia, using 1 or more of DM and dyslipidemia medicine, not deaf, and cooperative. Interventions that given to the patients are Patient Information Leaflet (PIL) and motivation messages by SMS which routinely given in a week after first we met. Knowledge is assessed using questionnaire and adherence is assesed using pill count method. The data that need analyzed are characteristic patients and the impact of intervention using Wilcoxon and paired t-test. The result of intervention in 56 patients showed the increasing number of patient that have good knowledge after intervention, from 58,9% to 71,4%, otherwise it not differ significantly (p 0.071). Other than that, the adherence also increased that showed from the patients who have adhere category after intervention, from 58,93% to 91.07% and it differ significantly with p 0.001 (p<0.05).